Video Edukasi 2 Dimensi Mengenai Sistem Isyarat Bahasa Indonesia (SIBI) pada Anak-Anak - Hendyanto; Suryawan, Hendra (Journal of Digital Ecosystem for Natural Sustainability, 2021)
Deafness is a condition that causes a person to have difficulty hearing. Deafness can occur in various age ranges and various causes. In the case of deafness that occurs at the age of children, it causes problems in terms of communication between the children verbally and in writing with other people. This can be permanent or temporary. This condition makes it difficult for children to get an exclusive learning media, and it is difficult for parents to help the learning process of deaf children. So we need a media that can help parents in helping their children in the learning process. Based on these problems, the researchers proposed a 2-dimensional animated educational video about SIBI for elementary school children which aims to help parents in making the learning of children with hearing impairments effective. In this study, researchers used 2D animated videos for deaf children so that they could learn how to communicate in sign language.